Epidemiology and quinolone-susceptibilities of Salmonella and Campylobacter in feedlot cattle - Smith, Ashley B. Thornton (Kansas State University, 2017)
Salmonella and Campylobacter are two leading causes of human foodborne disease. Cattle can asymptomatically shed these organisms in their feces. Fluoroquinolones are antimicrobials used to treat both humans and animals. With concerns over antimicrobial resistance, antimicrobial use in livestock has become scrutinized. Data on prevalence and susceptibility of Salmonella and Campylobacter in feedlot cattle, particularly those exposed to fluoroquinolones, are sparse. The purpose of the research described in this dissertation was to determine the prevalence and quinolone susceptibility of Salmonella and Campylobacter isolated from feedlot cattle and to determine whether these outcomes were associated with fluoroquinolone use. First, an observational study was performed at five commercial feedlots that used enrofloxacin (a fluoroquinolone) as first-line treatment for bovine respiratory disease (BRD). Fecal samples were collected from cattle pens with various levels of BRD and exposure to enrofloxacin. Salmonella and Campylobacter prevalence and susceptibility to quinolones, nalidixic acid and ciprofloxacin, were evaluated. Prevalence of Salmonella and Campylobacter was highly variable among and within feedlots. All but one Salmonella isolate was susceptible to nalidixic acid and ciprofloxacin, whereas 49% (126/256) of the Campylobacter isolates were resistant to both antimicrobials. However, the number of enrofloxacin treatments was not associated with the prevalence or susceptibilities of either organism. A second, experimental study assessed prevalence and quinolone susceptibilities of Salmonella and Campylobacter in feces of feedlot cattle administered enrofloxacin for the control of BRD (metaphylaxis). Cattle with no history of fluoroquinolone exposure were randomly assigned to either an enrofloxacin treated pen or a non-treated, control pen. Cattle feces were repeatedly collected and cultured for Salmonella and Campylobacter, with isolates tested for susceptibilities to nalidixic acid and ciprofloxacin. Overall, Salmonella and Campylobacter prevalence estimates were relatively low and decreased over time. Resistance prevalence was negligible for Salmonella, but was high for Campylobacter. However, there was no evidence that enrofloxacin metaphylaxis impacted the prevalence of Salmonella or Campylobacter, nor did it significantly affect their susceptibility to human quinolones. In conclusion, enrofloxacin use in feedlot cattle does not appear to have a significant impact on the prevalence or resistance of Salmonella and Campylobacter.
Keywords: cattle; fluoroquinolone; susceptibility; prevalence; Salmonella; Campylobacter